2015
DOI: 10.1007/s11745-015-4000-5
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid (CLA) Stimulates Mitochondrial Biogenesis Signaling by the Upregulation of PPARγ Coactivator 1α (PGC‐1α) in C2C12 Cells

Abstract: Along with its effect on body fat reduction, dietary conjugated linoleic acid (CLA) has been reported to improve physical activity and endurance capacity in mice. It has been suggested these effects may in part be due to physiological changes in skeletal muscle, however, the mode of action is not completely understood. Thus, the purpose of this study was to determine the relevant mechanisms of CLA isomers for mitochondrial biogenesis, one of the most important adaptive responses in skeletal muscle. Both cis-9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 48 publications
4
23
0
Order By: Relevance
“…Similar to mammals, AMPKα is an important regulator of metabolic homeostasis in Drosophila (Johnson et al, ); thus, we determined if CLA influenced AMPKα activation as previously reported in C2C12 myotubes (Huang et al, ; Kim and Park, ). There were significant differences in AMPKα activity between sexes ( p < 0.0001) and diet ( p = 0.0384), with interaction between sex and diet ( p = 0.0048) (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Similar to mammals, AMPKα is an important regulator of metabolic homeostasis in Drosophila (Johnson et al, ); thus, we determined if CLA influenced AMPKα activation as previously reported in C2C12 myotubes (Huang et al, ; Kim and Park, ). There were significant differences in AMPKα activity between sexes ( p < 0.0001) and diet ( p = 0.0384), with interaction between sex and diet ( p = 0.0048) (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…This result indicates a link between the nucleus and mitochondria by directly regulating mtDNA replication and transcription (46). Previously it was reported that conjugated linoleic acid isomers up-regulated PGC-1α, NRF1, and Tfam expression in C 2 C 12 cells (27). Also, a recent study showed that ω-3 PUFA from cod fish oil induced the activation of PGC-1α and -β in rat skeletal muscles (28).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 10t, 12c-conjugated linoleic acid has been also reported to stimulate mitochondrial biogenesis in C2C12 myoblasts. 19 These studies suggest that the cell biological response to different unsaturated fatty acids may depend from their different chemical structure (number and position of double bond and the presence or absence of a cis-9 double bond). In addition, the same fatty acid may have different actions on different cell type.…”
Section: Discussionmentioning
confidence: 99%